2021
DOI: 10.3390/ijerph18041616
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Approach Targeting Gut Microbiota in NAFLD—To Date

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a significant clinical and epidemiological problem that affects around 25% of the adult global population. A large body of clinical evidence highlights that NAFLD is associated with increased liver-related morbidity and mortality and an increased risk of cardiovascular disease, extrahepatic cancers, type 2 diabetes, and chronic kidney disease. Recently, a series of studies revealed the pivotal role of gut microbiota (GM) dysbiosis in NAFLD’s pathogenesis. The GM pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 228 publications
(252 reference statements)
0
6
0
Order By: Relevance
“…Similarly, results were reproduced in individuals with obesity and obesityrelated disorders [198,199,202,203]. Translating the evidence from these researches, it can now be assumed that prebiotics and probiotics are capable of regulating the metabolism also of NAFLD subjects [204][205][206][207][208][209]. For example, studies conducted to identify the effect of novel probiotics on NAFLD induced by a fructose-rich diet underlined the ability of intestinal flora to improve OS.…”
Section: Modulation Of Gut-liver Axis: Effects On Oxidative Stressmentioning
confidence: 92%
“…Similarly, results were reproduced in individuals with obesity and obesityrelated disorders [198,199,202,203]. Translating the evidence from these researches, it can now be assumed that prebiotics and probiotics are capable of regulating the metabolism also of NAFLD subjects [204][205][206][207][208][209]. For example, studies conducted to identify the effect of novel probiotics on NAFLD induced by a fructose-rich diet underlined the ability of intestinal flora to improve OS.…”
Section: Modulation Of Gut-liver Axis: Effects On Oxidative Stressmentioning
confidence: 92%
“…The most studied prebiotics in patients with NAFLD are fructooligosaccharides. Finally, synbiotics are a mix of probiotics and prebiotics [19][20][21].…”
Section: Prebiotics and Probiotics In Nafldmentioning
confidence: 99%
“…10 Numerous previous studies have shown that probiotics, prebiotics, and synbiotics (PPS) can improve the metabolic function of the liver and delay the progression of liver steatosis and fibrosis by improving the intestinal flora and alleviating the risk factors of NAFLD. [10][11][12][13][14] In this meta-analysis, we aim to explore whether synbiotics can improve metabolic function, liver fibrosis, and steatosis in NAFLD patients by including relevant studies from the last decade.…”
Section: Introductionmentioning
confidence: 99%